Electronic Health Records on the Top of Medical Device Incident Reports - Kumpuvaara Krista; Jormanainen Vesa; Vainiola Tarja; Ikonen Tuija S (Netherlands, 2025)
Medical Device incident reporting is a legal obligation for professional users in Finland. We analyzed all medical device incident reports recorded into the national incident repository from January 2014 to August 2021. Almost 30% of the total of 5,897 recorded incidents were caused by top ten devices, of which electronic health records were the most common (332 incidents). High number of incidents caused by electronic health records arouses safety concerns. A further analysis is required to explore the causes of findings.
Challenges of Trustable AI and Added-Value on Health